The reputation society how online opinions are reshaping the offline world - Masum, Hassan, 1971-; Tovey, Mark, 1970- (MIT Press, 2011)
In making decisions, we often seek advice. Online, we check Amazon recommendations, eBay vendors' histories, TripAdvisor ratings, and even our elected representatives' voting records. These online reputation systems serve as filters for information overload. In this book, experts discuss the benefits and risks of such online tools. The contributors offer expert perspectives that range from philanthropy and open access to science and law, addressing reputation systems in theory and practice. Properly designed reputation systems, they argue, have the potential to create a "reputation society," reshaping society for the better by promoting accountability through the mediated judgments of billions of people. Effective design can also steer systems away from the pitfalls of online opinion sharing by motivating truth-telling, protecting personal privacy, and discouraging digital vigilantism.
Keywords: Reputation.; Information society -- Social aspects.; Internet -- Social aspects.; elektronické knihy; electronic books